Social buffering in a bird. (July 2015) - Edgar, Joanne; Held, Suzanne; Paul, Elizabeth; Pettersson, Isabelle; I'Anson Price, Robbie; Nicol, Christine
Abstract : The presence of a conspecific can ameliorate an individual's stress response. This social buffering is known to be widespread in social mammals but the capacity of birds to act as social buffers has not yet been determined. We previously demonstrated that domestic hens, Gallus gallus domesticus, show socially mediated arousal when watching their chicks receiving an aversive air puff. Furthermore, the hens' expectation of the situation strongly influenced the chicks' behaviour. Here we examined whether hens act as a social buffer; reducing their chicks' stress response to an aversive stimulus. Pairs of chicks were exposed to an air puff treatment and a control, each with and without their mothers. Chicks showed a suite of responses to the air puff (including increased standing, reduced eye temperature, preening and ground pecking). Maternal absence exacerbated the chicks' preening and ground-pecking responses to this stressor. Individual hens varied in their effectiveness as a social buffer and this was associated with their socially mediated arousal when (matched pairs of) their chicks received an air puff. Specifically, the hens' heart rate increase was strongly negatively correlated with the degree to which chick preening and ground pecking increased with maternal presence. This is the first demonstration that avian mothers are able to reduce their chicks' stress responses to an aversive stimulus. Highlights: We compared stress responses of chicks in the presence and absence of their mother. We also measured the hens' socially mediated arousal (SMA) during chick stress. The presence of the chicks' mother reduced chick behavioural response to stress. Mother hens are therefore able to buffer their chicks' stress response. Hens' SMA was negatively correlated with their effectiveness as a social buffer.